2017
DOI: 10.1186/s13287-017-0674-3
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent nontumorigenic multilineage differentiating stress enduring cells (Muse cells): a seven-year retrospective

Abstract: Multilineage differentiating stress enduring (Muse) cells, discovered in the spring of 2010 at Tohoku University in Sendai, Japan, were quickly recognized by scientists as a possible source of pluripotent cells naturally present within mesenchymal tissues. Muse cells normally exist in a quiescent state, singularly activated by severe cellular stress in vitro and in vivo. Muse cells have the capacity for self-renewal while maintaining pluripotent cell characteristics indicated by the expression of pluripotent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 50 publications
(118 reference statements)
0
49
0
1
Order By: Relevance
“…These and future clinical trials will determine whether autologous or allogenic MSCs are most effective in the treatment of autoimmune diseases, and whether the inhibitory effects of MSCs are temporary or permanent. Other stem cells that may be useful for treating vitiligo are multilineage-differentiating stress enduring (MUSE) cells (Fisch et al, 2017). They can be easily isolated from mesenchymal tissue using the embryonic antigen-3 marker expressed by undifferentiated human embryonic stem cells; MUSE cells are able to self-renew and regenerate cells from all three germ layers while being non-tumorigenic (because of low telomerase activity).…”
Section: Stem Cell Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…These and future clinical trials will determine whether autologous or allogenic MSCs are most effective in the treatment of autoimmune diseases, and whether the inhibitory effects of MSCs are temporary or permanent. Other stem cells that may be useful for treating vitiligo are multilineage-differentiating stress enduring (MUSE) cells (Fisch et al, 2017). They can be easily isolated from mesenchymal tissue using the embryonic antigen-3 marker expressed by undifferentiated human embryonic stem cells; MUSE cells are able to self-renew and regenerate cells from all three germ layers while being non-tumorigenic (because of low telomerase activity).…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…They can be easily isolated from mesenchymal tissue using the embryonic antigen-3 marker expressed by undifferentiated human embryonic stem cells; MUSE cells are able to self-renew and regenerate cells from all three germ layers while being non-tumorigenic (because of low telomerase activity). Ex vivo studies have identified factors that induce MUSE cells to differentiate into melanocytes that incorporate into the epidermis and produce melanin in three-dimensional skin culture models (Fisch et al, 2017;Tsuchiyama et al, 2013). It remains to be determined whether these or other factors can be used to induce endogenous MUSE cells to differentiate into melanocytes for the treatment of vitiligo, or whether MUSE cells will have to be isolated, differentiated into melanocytes ex vivo, and returned to patients with vitiligo via autologous transplantation.…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…Like ESCs and iPSCs, MUSE cells express classic pluripotency markers, although at much lower levels, and hold the potential for triploblastic differentiation from a single cell [25] . As a small population of MSCs, MUSE cells have been found throughout different mesenchymal tissues [26] . However, it is necessary for the raw material, such as bone marrow stromal cells [24] , dermal fibroblasts [24,25] and lipoaspirate [27] , to be exposed to severe cellular stress conditions such as long-term collagenase incubation, isolation from nutrients, low temperatures, and hypoxia in order to purify the MUSE cells from the MSCs.…”
Section: Multi-lineage Differentiating Stress Enduring Cellsmentioning
confidence: 99%
“…However, it is necessary for the raw material, such as bone marrow stromal cells [24] , dermal fibroblasts [24,25] and lipoaspirate [27] , to be exposed to severe cellular stress conditions such as long-term collagenase incubation, isolation from nutrients, low temperatures, and hypoxia in order to purify the MUSE cells from the MSCs. Interestingly, in the "elite model" of iPSC generation, MUSE cells are considered to be the subpopulation of MSCs that give rise to iPSCs [25] ; however, no teratoma formation was observed when MUSE cells were injected into mice throughout a 6-month period [26] . It is worth pointing out that the mechanism governing the transition from nontumorigenic MUSE cells to tumorigenic iPSCs remains an enigma, and that the genomic stability of MUSE cells has not been fully investigated.…”
Section: Multi-lineage Differentiating Stress Enduring Cellsmentioning
confidence: 99%
“…Due to the progressive loss of functional melanocytes associated with an inflammatory/autoimmune context and the failure to spontaneously recover skin functionality, it has been proposed to consider vitiligo as a degenerative disease . In addition to pharmacological treatment, several different surgical and regenerative approaches have been proposed to restore pigmentation in vitiligo including dermabrasion, epidermal or hair follicle outer root sheath cell suspension transplant, cultured epithelial cells or cultured epithelia sheet graft, minipunch graf, suction blistering grafting, platelet‐rich plasma‐enriched (PRP) supplementation and the use of autologous mesenchymal stem cells (MSCs) . Repigmentation through dermis stimulation reflects the emerging key role of the dermal compartment in vitiligo since dermoabrasion and mechanical needling deeply stimulate the dermis and induce processes similar to a wound‐healing response with the release of different growth factors and inflammatory mediators .…”
Section: Introductionmentioning
confidence: 99%